Negative active material as well as preparation method and application thereof

By using a combined structure of artificial graphite and amorphous carbon layer in the negative electrode active material of the battery, and combining it with appropriate binders and coating agents, the problem of improving battery energy density and rate performance is solved, and higher fast charging performance and energy density are achieved, while inhibiting cyclic expansion.

CN119674013AInactive Publication Date: 2025-03-21EVE ENERGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411874538.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When existing batteries improve energy density and rate performance, there are problems such as increasing current collector resistance and easy puncture of the separator, resulting in a degradation of the fast charging performance of the battery.

Method used

Artificial graphite is used as the core layer of the negative electrode active material, and an amorphous carbon layer is added through liquid phase coating carbonization treatment, and combined with binder and coating agent is used to optimize the structure of the negative electrode active material to improve the energy density and rate performance of the battery.

Benefits of technology

Through the improved structure of the negative electrode active material, the fast charging performance and energy density of the battery are significantly improved, and the cyclic expansion is effectively suppressed, maintaining good 3C charging rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005196971270000091
    Figure BDA0005196971270000091
  • Figure BDA0005196971270000101
    Figure BDA0005196971270000101
Patent Text Reader

Abstract

The invention provides a negative electrode active material as well as a preparation method and application thereof. The negative electrode active material takes artificial graphite as a core layer and amorphous carbon as a coating layer; the preparation method of the negative electrode active material comprises the following steps: S1, crushing and grading needle coke to obtain aggregate; s2, the aggregate and a binder are mixed and then subjected to secondary granulation treatment and high-temperature graphitization treatment in sequence, artificial graphite is obtained, and the binder comprises at least one of coal tar and asphalt; s3, the artificial graphite is obtained through liquid-phase coating carbonization treatment; wherein the liquid-phase coating carbonization treatment comprises the specific steps that the artificial graphite and a coating agent are mixed and then subjected to carbonization treatment, and the coating agent comprises at least one of epoxy resin and phenolic resin. Starting from the preparation of the artificial graphite, the energy density and the rate capability of the battery can be improved by matching the binder and the coating agent. Specifically, on one hand, pores of the negative electrode active material can be increased by introducing the binder, so that the lithium storage capacity is improved, and the expansion rate is reduced; and on the other hand, the amorphous carbon layer is coated on the surface of the artificial graphite by using the liquid-phase coating agent, so that the ion transmission rate of the negative electrode active material in the charge-discharge process is optimized, and the fast charge capacity of the battery cell is improved. By matching the binder and the coating agent, the energy density and the rate capability of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of batteries, and in particular relates to a negative electrode active material and a preparation method and application thereof. Background Art

[0002] With the continuous development of consumer electronic products (such as smartphones, tablets, etc.), and due to the fast pace of life of modern consumers, users have higher expectations for the battery life and fast charging capabilities of their devices. Among them, without increasing the size and weight of the battery, increasing the energy density of the battery cell has become the key to meeting the long-term battery life requirements. For example, smartphones are becoming increasingly powerful, with increased screen resolution and processor performance, which have increased energy consumption, so batteries with higher energy density are needed to maintain a longer usage time. Achieving good fast charging performance requires that the battery not only has a high energy density, but also has good rate performance.

[0003] The main means to improve battery energy density are to make auxiliary materials (copper foil, aluminum foil, diaphragm, etc.) thinner and reduce the amount of conductive agent in the formula. However, all the above mentioned methods have certain problems.

[0004] Although thinning of auxiliary materials can reduce the weight and volume of the battery to a certain extent and thus indirectly increase the energy density, thinning will increase the resistance of the current collector (reduce the cross-sectional area of ​​the current collector) or make the diaphragm more easily punctured, thus affecting the rate performance of the battery.

[0005] In addition, reducing the amount of conductive agent is to make more space for active materials, thereby increasing energy density. However, after the conductive agent is reduced, the electron conduction network inside the electrode will become less perfect. During high-rate charging and discharging, it is difficult for electrons to quickly reach the surface of the active material to react, resulting in a decrease in the rate performance of the battery. Summary of the invention

[0006] In order to improve the energy density and rate performance of a battery, the present invention provides a negative electrode active material and a preparation method and application thereof.

[0007] According to one aspect of the present application, a method for preparing a negative electrode active material is provided, wherein the negative electrode active material uses artificial graphite as a core layer and amorphous carbon as a coating layer; the method for preparing the negative electrode active material comprises the following steps: S1. Aggregate is obtained by crushing and grading needle coke; S2. Aggregate is mixed with a binder and then subjected to secondary granulation and high-temperature graphitization in sequence to obtain artificial graphite, wherein the binder comprises at least one of coal tar and asphalt; S3. Artificial graphite is obtained by liquid phase coating and carbonization; wherein the specific steps of liquid phase coating and carbonization are as follows: artificial graphite is mixed with a coating agent and then carbonized, and the coating agent comprises at least one of epoxy resin and phenolic resin. At present, in the prior art, most of the consumer graphite negative poles are mid-to-high-end artificial graphite to match the current terminal's stringent performance requirements for battery cell products, but from the characteristics and technology of the graphite material itself, it is very difficult and the threshold is high to take into account both energy density and kinetics. The present application starts from the preparation of artificial graphite and can improve the energy density and rate performance of the battery by matching a binder and a coating agent. Specifically, on the one hand, the introduction of a binder can increase the pores of the negative electrode active material, thereby increasing its lithium storage capacity and reducing its expansion rate; on the other hand, by using a liquid phase coating agent to coat an amorphous carbon layer on the surface of artificial graphite, the ion transmission rate of the negative electrode active material during the charge and discharge process is optimized, thereby improving the fast charging capability of the battery cell. Therefore, by matching a binder and a coating agent, the energy density and rate performance of the battery can be improved.

[0008] Preferably, the binder is asphalt; and / or the coating agent is phenolic resin.

[0009] Preferably, the particle size D of the artificial graphite is 50 It is 11~14um.

[0010] Preferably, the coating layer has a thickness of 50 to 100 nm.

[0011] Preferably, in S2, the amount of binder used is 3-17% of the weight of the aggregate.

[0012] Preferably, in S2, the reaction conditions of the secondary granulation treatment are: the reaction temperature is 800-950°C, and the granulation time is not less than 9 hours.

[0013] Preferably, in S2, the reaction conditions of the high temperature graphitization treatment are: reaction temperature is 2900-3200° C., and reaction time is 8-14 hours.

[0014] Preferably, in S3, the amount of the coating agent is not less than 5% by weight of the artificial graphite.

[0015] Preferably, in S3, the reaction conditions of the carbonization treatment are: reaction temperature is 1000-1300° C., and reaction time is 6-9 hours.

[0016] Preferably, in S1, the aggregate particle size is ≤7.5um and the tap density is ≥0.9g / cm 3 .

[0017] The second aspect of the present application provides a negative electrode active material, which is prepared by the negative electrode active material preparation method as described above.

[0018] According to a third aspect of the present application, a negative electrode is provided, comprising the negative electrode active material as described above, wherein the mass content of the negative electrode active material in the negative electrode is not less than 98%.

[0019] Preferably, the negative electrode includes an adhesive, and the adhesive includes carboxymethyl cellulose and styrene-butadiene rubber, and the carboxymethyl cellulose:styrene-butadiene rubber is calculated by mass ratio of 1 to 7:2 to 11. By combining carboxymethyl cellulose and styrene-butadiene rubber to form an adhesive, and using the negative electrode active material provided by the present application, it is possible to achieve good 3C charge rate performance of the battery without using a conductive agent, and the cycle expansion is effectively suppressed.

[0020] Preferably, the viscosity of the carboxymethyl cellulose at a solid content of 1% is 7000 to 12000 mPa·s.

[0021] Preferably, the carboxymethyl cellulose is lithiated.

[0022] Preferably, the particle size of the styrene-butadiene rubber is 100-200 nm, the solid content is 28-35%, the pH value is 6.5-8, and the viscosity is 100-150 mPa·s.

[0023] Preferably, the styrene-butadiene rubber is lithiated.

[0024] Preferably, the mass content of the binder in the negative electrode is 0.5-2%.

[0025] Preferably, in the negative electrode, the mass content of carboxymethyl cellulose is 0.5-1%.

[0026] Preferably, in the negative electrode, the mass content of styrene-butadiene rubber is less than 1.3%.

[0027] According to a fourth aspect of the present application, a battery is provided, comprising the negative electrode as described above. DETAILED DESCRIPTION

[0028] In order to enable those skilled in the art to better understand the technical solutions in this application, the technical solutions in this application will be clearly and completely described below in conjunction with the embodiments of this application. Obviously, the described embodiments are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of this application.

[0029] Example 1

[0030] 1. Preparation of negative electrode active materials

[0031] This embodiment prepares the negative electrode active material by the following steps:

[0032] S1. Needle coke (structure length and width <10μm) is crushed and classified to obtain aggregate (aggregate particle size ≤7.5um, tap density ≥0.9g / cm 3 );

[0033] S2. Aggregates and coal tar are mixed and then subjected to secondary granulation treatment and high-temperature graphitization treatment in sequence to obtain artificial graphite, wherein the amount of coal tar is 10% of the weight of the aggregates; the granulation temperature in the secondary granulation treatment is 850°C and the granulation time is 9 hours; the reaction temperature in the high-temperature graphitization treatment is 3100°C and the reaction time is 10 hours.

[0034] S3. Artificial graphite is obtained by liquid-phase coating carbonization treatment; wherein, the specific steps of the liquid-phase coating carbonization treatment are: artificial graphite is mixed with epoxy resin and then carbonized, and the amount of epoxy resin used is 5% of the artificial graphite; the reaction temperature in the carbonization treatment is 1200°C, and the reaction time is 6 hours.

[0035] 2. Preparation of negative electrode and lithium-ion battery

[0036] (1) Preparation of negative electrode

[0037] The negative electrode active material prepared above was mixed with the adhesive in a mass ratio of 98.5%:1.5%, and after adding deionized water, a negative electrode slurry with a solid content of 48.5% was prepared, wherein the adhesive was composed of sodium carboxymethyl cellulose (CMC, 1% solid content viscosity 10000mPa·s) and styrene butadiene rubber (SBR, particle size 200nm, solid content 30%, viscosity 150mPa·s), and the mass ratio was CMC:SBR=3:4. The negative electrode slurry was coated on the current collector on the copper foil through a coating process, and the negative electrode sheet was obtained after vacuum drying and cold pressing processes.

[0038] (2) Preparation of lithium-ion batteries

[0039] The positive electrode sheet (commercial lithium cobalt oxide), the isolation film, and the negative electrode sheet are stacked in order, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then they are wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, the electrolyte (general formula) is injected, and after vacuum packaging, standing, formation, shaping and other processes, a lithium-ion battery is obtained.

[0040] Example 2

[0041] This embodiment refers to the formula and method provided in Example 1 to prepare the negative electrode active material and the negative electrode and lithium ion battery using the negative electrode active material. The difference from Example 1 is that when preparing the negative electrode active material, the epoxy resin is replaced by phenolic resin in equal parts by mass. Except for the above differences, the operation steps of preparing the negative electrode active material and the negative electrode and lithium ion battery using the negative electrode active material in this embodiment are strictly consistent with those in Example 1.

[0042] Example 3

[0043] This embodiment prepares negative electrode active materials and negative electrodes and lithium-ion batteries using the negative electrode active materials with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the negative electrode active materials, this embodiment uses asphalt in equal parts by mass to replace coal tar. Except for the above differences, the operation steps of preparing the negative electrode active materials and negative electrodes and lithium-ion batteries using the negative electrode active materials in this embodiment are strictly consistent with those in Example 1.

[0044] Example 4

[0045] This embodiment prepares negative electrode active materials and negative electrodes and lithium-ion batteries using the negative electrode active materials with reference to the formula and method provided in Example 2. The difference from Example 2 is that when preparing the negative electrode active materials, this embodiment uses asphalt in equal parts by mass to replace coal tar. Except for the above differences, the operation steps of preparing the negative electrode active materials and negative electrodes and lithium-ion batteries using the negative electrode active materials in this embodiment are strictly consistent with those in Example 2.

[0046] Example 5

[0047] This embodiment refers to the formula and method provided in Example 1 to prepare the negative electrode active material and the negative electrode and lithium ion battery using the negative electrode. The difference from Example 1 is that when preparing the negative electrode in this embodiment, the mass ratio is calculated as CMC:SBR=4:5 (the total mass fraction of the adhesive remains unchanged). Except for the above differences, the operation steps of preparing the negative electrode active material and the negative electrode and lithium ion battery using the negative electrode in this embodiment are strictly consistent with those in Example 1.

[0048] Example 6

[0049] This embodiment refers to the formula and method provided in Example 1 to prepare the negative electrode active material and the negative electrode and lithium ion battery using the negative electrode. The difference from Example 1 is that when preparing the negative electrode in this embodiment, the mass ratio is calculated as CMC:SBR=1:2 (the total mass fraction of the adhesive remains unchanged). Except for the above differences, the operation steps of preparing the negative electrode active material and the negative electrode and lithium ion battery using the negative electrode in this embodiment are strictly consistent with those in Example 1.

[0050] Example 7

[0051] This embodiment refers to the formula and method provided in Example 1 to prepare the negative electrode active material and the negative electrode and lithium ion battery using the negative electrode. The difference from Example 1 is that when preparing the negative electrode in this embodiment, the mass ratio is calculated as CMC:SBR=7:11 (the total mass fraction of the adhesive remains unchanged). Except for the above differences, the operation steps of preparing the negative electrode active material and the negative electrode and lithium ion battery using the negative electrode in this embodiment are strictly consistent with those in Example 1.

[0052] Example 8

[0053] This embodiment refers to the formula and method provided in Example 1 to prepare the negative electrode active material and the negative electrode and lithium ion battery using the negative electrode. The difference from Example 1 is that when preparing the negative electrode in this embodiment, the mass ratio is calculated as CMC:SBR=1:3 (the total mass fraction of the adhesive remains unchanged). Except for the above differences, the operation steps of preparing the negative electrode active material and the negative electrode and lithium ion battery using the negative electrode in this embodiment are strictly consistent with those in Example 1.

[0054] Example 9

[0055] This embodiment prepares negative electrode active materials and negative electrodes and lithium-ion batteries using the negative electrode active materials with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the negative electrode, the untreated CMC is replaced with an equal mass fraction of CMC that has been subjected to lithium treatment. Except for the above differences, the operation steps of preparing the negative electrode active materials and negative electrodes and lithium-ion batteries using the negative electrode active materials in this embodiment are strictly consistent with those in Example 1.

[0056] Example 10

[0057] This example prepares the negative electrode active material and the negative electrode and lithium ion battery using the negative electrode and the method provided in Example 1. The difference from Example 1 is that when preparing the negative electrode, the untreated SBR is replaced with an equal mass fraction of SBR that has been treated with lithium. Except for the above differences, the operation steps of preparing the negative electrode active material and the negative electrode and lithium ion battery using the negative electrode and the method provided in Example 1 are strictly consistent with those in Example 1.

[0058] Embodiment 11

[0059] This embodiment refers to the formula and method provided in Example 1 to prepare the negative electrode active material and the negative electrode and lithium ion battery using the negative electrode. The difference from Example 1 is that when preparing the negative electrode, the same mass fraction of CMC treated with lithium is used to replace the untreated CMC, and the same mass fraction of SBR treated with lithium is used to replace the untreated SBR. Except for the above differences, the operation steps of preparing the negative electrode active material and the negative electrode and lithium ion battery using the negative electrode in this embodiment are strictly consistent with those in Example 1.

[0060] Example 12

[0061] This example prepares the negative electrode active material and the negative electrode and lithium ion battery using the negative electrode with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the negative electrode, this example uses an equal mass fraction of low-viscosity CMC (1% solid content viscosity is 5000mPa·s) to replace CMC. Except for the above differences, the operation steps of preparing the negative electrode active material and the negative electrode and lithium ion battery using the negative electrode in this example are strictly consistent with those in Example 1.

[0062] Comparative Example 1

[0063] This comparative example prepares the negative electrode and lithium-ion battery with reference to the formula and method provided in Example 1. The difference from Example 1 is that the formula used in this comparative example for preparing the negative electrode is: ordinary natural graphite, carbon black and adhesive are mixed in a mass ratio of 96:1.3:2.7. In addition to the above differences, the operation steps for preparing the negative electrode active material and the negative electrode and lithium-ion battery using the negative electrode active material in this comparative example are strictly consistent with those in Example 1.

[0064] Comparative Example 2

[0065] This comparative example refers to the formula and method provided in Example 1 to prepare the negative electrode active material and the negative electrode and lithium ion battery using the negative electrode active material. The difference from Example 1 is that this comparative example uses a solid phase coating method to prepare the negative electrode active material. In addition to the above differences, the operation steps for preparing the negative electrode active material and the negative electrode and lithium ion battery using the negative electrode active material in this comparative example are strictly consistent with those in Example 1. Specifically, the method for preparing the negative electrode active material in this comparative example is:

[0066] S1-S2 are carried out strictly according to the operation steps of Example 1;

[0067] S3. Artificial graphite is obtained by solid-phase coating and carbonization treatment; wherein, the specific steps of the solid-phase coating and carbonization treatment are: artificial graphite is mixed with asphalt and then carbonized, and the amount of asphalt is 5% of the artificial graphite; the reaction temperature in the carbonization treatment is 1200°C and the reaction time is 7 hours.

[0068] Comparative Example 3

[0069] This comparative example prepares negative electrode active materials and negative electrodes and lithium-ion batteries using the negative electrode active materials with reference to the formula and method provided in Example 1. The difference from Example 1 is that when preparing the negative electrode active materials, this comparative example uses coal tar in equal parts by mass to replace epoxy resin. Except for the above differences, the operation steps for preparing the negative electrode active materials and negative electrodes and lithium-ion batteries using the negative electrode active materials in this comparative example are strictly consistent with those in Example 1.

[0070] Test Case

[0071] 1. Test subjects

[0072] The negative electrode active materials prepared in Examples 1 to 12 and Comparative Examples 1 to 3 and the negative electrodes and lithium ion batteries using the same.

[0073] 2. Test Method

[0074] (1) 3C charging cross-current ratio: The battery cell is tested in the Xinwei cabinet. Under the 3C fast charging setting, the ratio of the charged capacity in the constant current stage to the total charged capacity reflects the fast charging performance.

[0075] (2) Battery cell energy density: the ratio of the product of the battery cell capacity and the corresponding voltage platform to the battery cell volume.

[0076] (3) 25℃ 3C / 1C cycle for 800 cycles: At room temperature, the battery cell was charged at 3C constant current and constant voltage in a Xinwei test cabinet with an upper voltage of 4.5V and a cutoff of 0.025C. After 5min of storage, the battery cell was discharged at 1C to 3.0V. The remaining capacity and thickness expansion after 800 cycles were used as indicators for judging the cycle performance.

[0077] (4) 45℃ 3C / 1C cycle for 600 cycles: In a 45℃ temperature chamber, the battery cell was charged with 3C constant current and constant voltage on a Xinwei test cabinet with an upper voltage of 4.5V and a cutoff of 0.025C. After 5min of storage, the battery cell was discharged at 1C to 3.0V. The remaining capacity and thickness expansion after 600 cycles were used as indicators for judging the cycle performance.

[0078] (5) 15℃ 3C / 1C cycle for 400 cycles: In a 15℃ incubator, the battery cells were charged at 3C constant current and constant voltage with an upper voltage of 4.5V and a cutoff of 0.025C on a Xinwei test cabinet. After 5 minutes of standing, the cells were discharged at 1C to 3.0V. The remaining capacity and thickness expansion after 400 cycles were used as indicators for judging the cycle performance.

[0079] 3. Test results and analysis

[0080] The test results of this test case are shown in Table 1 and Table 2.

[0081] It can be seen from the data in Table 1 that the negative electrode active material provided in the present application can significantly improve the fast charging performance and energy density of the battery. Furthermore, based on the data in Table 2, it can be seen that by regulating the mass ratio and material type of the raw materials used in the preparation of the negative electrode active material and the negative electrode adhesive, the cycle performance and low-temperature rate performance of the battery at high rates can be improved. It can be seen from the data of Examples 1 to 4 and Comparative Examples 1 to 3 that when preparing the negative electrode active material, the material selection of the binder mixed with the aggregate, the material selection of the coating agent used in the liquid phase coating treatment, and the combination of the two will affect the rate performance of the battery cell.

[0082] Secondly, based on the data of Examples 5 to 8, it can be seen that the mass ratio of CMC to SBR in the adhesive will also affect the rate performance of the battery cell.

[0083] In addition, it can be seen from the data of Examples 9 to 11 that the adhesive after lithium treatment can reduce roller rebound and cycle expansion, and can further enhance the energy density and fast charging performance of the battery. In addition, it can be seen from the data of Example 12 that the choice of adhesive in the negative electrode will also affect the performance of the battery. This is because the high viscosity CMC after lithium treatment can effectively stabilize the slurry, which is conducive to coating, and at the same time the impedance is small. Therefore, the present application can maintain good fast charging performance and energy density of the battery without adding a conductive agent by using the negative electrode active material and adhesive prepared by a specific method.

[0084] Table 1. Test results of fast charging performance and energy density

[0085] Group 3C charging cross current ratio Battery cell energy density Wh / L Example 1 66.2% 645.2 Example 10 68.3% 644.4 Embodiment 11 68.8% 645.8 Comparative Example 1 60.5% 630.0 Comparative Example 2 63.0% 638.0 Comparative Example 3 62.0% 636.8

[0086] Table 2. Cycle performance test results

[0087]

[0088]

[0089] The above embodiments are only used to illustrate the technical solution of the present application rather than to limit the protection scope of the present application. Although the present application has been described in detail with reference to the preferred embodiments, a person skilled in the art should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A method for preparing a negative electrode active material, characterized in that: The negative electrode active material has artificial graphite as a core layer and amorphous carbon as a coating layer; The method for preparing the negative electrode active material comprises the following steps: S1. Aggregate is obtained by crushing and classifying needle coke; S2. The aggregate and the binder are mixed and then subjected to secondary granulation treatment and high-temperature graphitization treatment to obtain artificial graphite, wherein the binder includes at least one of coal tar and asphalt; S3. The artificial graphite is sequentially subjected to liquid phase coating treatment and carbonization treatment to obtain the negative electrode active material; The specific steps of the liquid phase coating treatment are as follows: the artificial graphite is mixed with a coating agent, and the coating agent includes at least one of epoxy resin and phenolic resin.

2. The method for preparing the negative electrode active material according to claim 1, characterized in that: The binder is asphalt; and / or the coating agent is phenolic resin.

3. The method for preparing the negative electrode active material according to claim 1, characterized in that: In S2, the amount of the binder is 3-17% of the weight of the aggregate.

4. The method for preparing the negative electrode active material according to claim 1, characterized in that: In S3, the amount of the coating agent is not less than 5% of the weight of the artificial graphite.

5. The method for preparing the negative electrode active material according to claim 1, characterized in that: In S1, the aggregate particle size is ≤7.5um, and the tap density is ≥0.9g / cm 3 .

6. A negative electrode active material, characterized in that: The negative electrode active material is prepared by the method for preparing the negative electrode active material according to any one of claims 1 to 5.

7. The negative electrode active material according to claim 6, characterized in that: The coating layer has a thickness of 50-100 nm.

8. A negative electrode, characterized in that The negative electrode comprises the negative electrode active material as claimed in claim 6 or 7, wherein the mass content of the negative electrode active material in the negative electrode is not less than 98%.

9. The negative electrode according to claim 8, characterized in that The negative electrode includes an adhesive, and the adhesive includes carboxymethyl cellulose and styrene-butadiene rubber. Calculated by mass ratio, the carboxymethyl cellulose: the styrene-butadiene rubber = 1-7:2-11.

10. A battery, characterized in that: The battery comprises the negative electrode as claimed in claim 8 or 9.

Citation Information

Patent Citations

  • High performance lithium ion power battery negative electrode material

    CN107749462A

  • Electrode material and secondary battery

    CN109704323A

  • Fast charging graphite and preparation method thereof, negative plate and battery

    CN116588923A